2018
DOI: 10.15294/lc.v12i2.14176
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Students’ Speaking Skill Using Three Step Interview and Numbered Heads Together

Abstract: This research aimed to investigate the effectiveness of Three Step Interview (TSI) and Numbered HeadsTogether Techniques (NHT) to enhance speaking skill for the students having different motivation levels and to show if there is any interaction between teaching techniques and motivation. The participants of the research were the students of survival English Class Level of Nissan Fortuna English Course, Kudus. The research method of this study was quantitative by using 2x2 factorial experimental research design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
5
0
3
Order By: Relevance
“…Rahmatunisa (2015) found that undergraduate students in Jakarta encountered various problems in writing. Ratnawati, Yuliasri, & Hartono (2018) discovered that undergraduate students in West Java also encountered difficulties in their academic writing. Furthermore, Samanhudi & Linse (2019) found that Indonesian postgraduate students at a UK University faced problems related to critical thinking realization in their essay writing.…”
Section: The Process and Problems Of Efl Learners In English Writing:mentioning
confidence: 99%
“…Rahmatunisa (2015) found that undergraduate students in Jakarta encountered various problems in writing. Ratnawati, Yuliasri, & Hartono (2018) discovered that undergraduate students in West Java also encountered difficulties in their academic writing. Furthermore, Samanhudi & Linse (2019) found that Indonesian postgraduate students at a UK University faced problems related to critical thinking realization in their essay writing.…”
Section: The Process and Problems Of Efl Learners In English Writing:mentioning
confidence: 99%
“…Salah satu Keterampilan berbahasa dalam pembelajaran Bahasa Inggris yaitu keterampilan berbicara. Keterampilan berbicara merupakan salah satu indikator terpenting untuk keberhasilan siswa dalam belajar bahasa Inggris (Ratnawati et al, 2018;Ruspa, 2019;Yunita et al, 2017). Keterampilan berbicara adalah kemampuan menyusun kalimat-kalimat karena komunikasi terjadi melalui kalimat-kalimat untuk menampilkan perbedaan tingkah laku yang bervariasi dari masyarakat yang berbeda (Saputra, 2017).…”
Section: Pendahuluanunclassified
“…Melalui strategi pembelajaran three step interview, siswa diberi kesempatan untuk meningkatkan kemampuan berbicara, karena di dalam tahapan-tahapan kegiatan siswa lebih aktif untuk berbicara dan mengemukakan pendapatnya. Keuntungan menggunakan strategi three step interview dalam pembelajaran yaitu: (1) Three step interview adalah strategi pembelajaran yang berfungsi mengaktifkan pengetahuan siswa tentang suatu topik melalui percakapan dalam pelajaran bahasa; (2) siswa memiliki kesempatan untuk melatih kemmapuan berbicara tanpa rasa cemas; dan (3) strategi three step interview dapat membuat suasana kelas lebih menyenangkan dan diharapkan dapat membuat siswa lebih kooperatif selama berbicara di kelas (Ratnawati et al, 2018) Selain itu, Kartika (2013) menyatakan bahwa pembelajaran tentang percakapan berpasangan meningkatkan kepercayaan diri siswa dalam berbicara Bahasa inggris. Selanjutnya strategi three step interview dapat meningkatkan keterampilan berbicara siswa yang memiliki motivasi rendah (Ratnawati et al, 2018).…”
Section: Refleksi Tindakanunclassified
“…Some earlier studies about interview in English class have been conducted where most of them were in class (offline or face-to-face learning). Three of them observed with the three-step-interview technique were Hendriani (2018), Permanasari (2014) and Ratnawati et al (2018). Three-step-interview technique was first introduced by Spencer Kagan in 1989 which was one of the cooperative learning strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Students interview each other in pairs, one way and the other; then the students share with the group information they learned from their interview (Kagan, 1989). A study of Ratnawati et al (2018) implemented three-step-interview (TSI) and numbered heads together (NHT) which result was TSI performed better than NHT to improve the students' speaking skills in English. Moreover, Hendriani (2018) and Permanasari (2014) applied TSI for tenth-grade high school students in English course.…”
Section: Introductionmentioning
confidence: 99%